2020
DOI: 10.3390/epigenomes4030019
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation and LncRNA-Associated DNA Methylation in Metformin-Treated and -Untreated Diabetes

Abstract: Metformin, which is used as a first line treatment for type 2 diabetes mellitus (T2DM), has been shown to affect epigenetic patterns. In this study, we investigated the DNA methylation and potential lncRNA modifications in metformin-treated and newly diagnosed adults with T2DM. Genome-wide DNA methylation and lncRNA analysis were performed from the peripheral blood of 12 screen-detected and 12 metformin-treated T2DM individuals followed by gene ontology (GO) and KEGG pathway analysis. Differentially methylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Here we report, for the first time, a concordant negative association between two measurements reflecting carbohydrates’ quality and quantity (GI and GL), and global methylation levels measured within the same subjects from a general population. These associations resisted correction for several factors influencing hypomethylation, including use of metformin [ 24 , 25 ] or self-reported diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report, for the first time, a concordant negative association between two measurements reflecting carbohydrates’ quality and quantity (GI and GL), and global methylation levels measured within the same subjects from a general population. These associations resisted correction for several factors influencing hypomethylation, including use of metformin [ 24 , 25 ] or self-reported diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid is an essential water-soluble vitamin for vertebrates. It is incorporated as an essential cofactor for nucleotide synthesis and the generation of S-adenosylmethionine (SAM), which functions as a methyl group donor for DNA, RNA, and proteins [55]. Maternal folate deficiency causes severe neural tube defects [56] and craniofacial abnormalities [57] in offspring.…”
Section: Prevention Of Transgenerational Transmission Of Disease Susc...mentioning
confidence: 99%
“…Additionally, mGPDH and complex IV have also been considered targets of metformin in animal experiments ( Madiraju et al, 2014 ; LaMoia et al, 2022 ), and more targets have been found in the research into the actions of metformin in mitochondria ( Pecinova et al, 2019 ; MacDonald et al, 2021 ). LncRNAs regulated by metformin potentially affect mitochondrial function; clinical research on DNA methylation in plasma from metformin-treated patients with T2DM showed that 57 lncRNA-associated DNA methylation regions were found, which included the mitochondrial ATP synthase-coupling factor 6 (ATP5J) ( Solomon et al, 2020 ), suggesting that metformin may regulate ATP5J through lncRNAs. In addition, metformin increases GAS5 expression in HepG2 cells and the plasma of patients with T2DM ( Parvar et al, 2023 ), and elevated GAS5 decreases mitochondrial tricarboxylic acid flux by disrupting the metabolic enzyme tandem of the tricarboxylic acid cycle ( Sang et al, 2021 ), providing another explanation for the mitochondrial inhibition effects of metformin.…”
Section: The Anti-diabetic Action Of Metformin Mediated By Lncrnasmentioning
confidence: 99%